2023
DOI: 10.1002/mnfr.202200809
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic Diet Cycling Produces Graded Effects on Cognition and Microbiota Composition in Rats

Abstract: Scope The effects of diet cycling on cognition and fecal microbiota are not well understood. Method and Results Adult male Sprague‐Dawley rats were cycled between a high‐fat, high‐sugar “cafeteria” diet (Caf) and regular chow. The impairment in place recognition memory produced by 16 days of Caf diet was reduced by switching to chow for 11 but not 4 days. Next, rats received 16 days of Caf diet in 2, 4, 8, or 16‐day cycles, each separated by 4‐day chow cycles. Place recognition memory declined from baseline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Polyphenol intake has been described to induce a "prebiotic-like" effect and it can modify the α-diversity of gut microbiota (increasing or decreasing it) depending on the treatment dosage, length of administration, or the type of bioactive compound administered [62]. Similarly to other authors [63], β-diversity measured by the principal-component analysis (PCA) using Bray-Curtis methodology showed that the interventions implemented in our study decreased the separation in microorganism composition found between SD and HFHF groups, making that composition closer to the SD group. In obese mice, a dysbiotic gut microbiota seems to decrease the biosynthesis of secondary bile acids that cause bacterial overgrowth [60].…”
Section: Discussionmentioning
confidence: 93%
“…Polyphenol intake has been described to induce a "prebiotic-like" effect and it can modify the α-diversity of gut microbiota (increasing or decreasing it) depending on the treatment dosage, length of administration, or the type of bioactive compound administered [62]. Similarly to other authors [63], β-diversity measured by the principal-component analysis (PCA) using Bray-Curtis methodology showed that the interventions implemented in our study decreased the separation in microorganism composition found between SD and HFHF groups, making that composition closer to the SD group. In obese mice, a dysbiotic gut microbiota seems to decrease the biosynthesis of secondary bile acids that cause bacterial overgrowth [60].…”
Section: Discussionmentioning
confidence: 93%
“…The study was advertised via the University of Sydney research volunteer website, social media, and flyers distributed around campus. Prospective participants were sent information about the study and contacted for a brief phone interview to estimate weekly SSB intake (>2 L/week) and confirm age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and no health-related issues. Those meeting these criteria were invited to an in-person screening session, where the BEVQ-15, DFSQ, and BIOFORM questionnaires were administered, and weight and height were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from rodent studies indicates that the cognitive impairments associated with SSB intake can be ameliorated by replacing the sugar solution with water or a non-nutritive sweetener [16]. Beneficial cognitive effects have been reported when animals fed a high-fat, high-sugar 'cafeteria'-style diet are switched to regular chow [17,18] and improvements are not contingent on reductions in body weight or fat mass [19]. However, whether interventions that reduce SSB intake can improve hippocampal-dependent forms of cognition in humans remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, healthier dietary patterns (e.g., appropriate cholesterol and fat intake, adequate amounts of dietary fiber and vitamins, and reduced unnecessary sugar intake) are accompanied by similar beneficial changes ( Fu et al, 2022 ; Huang X. et al, 2022 ; Kim et al, 2022 ). In animal models, modification of gut bacteria through dietary interventions has shown promising results in terms of improved memory and reduced inflammation ( Proctor et al, 2017 ; Kendig et al, 2023 ).…”
Section: Prevention and Treatment Strategies Based On Peripheral Infl...mentioning
confidence: 99%